The Validity of Learning Media on the Form of Booklet Types of Bryophytes in the Riverbanks of Wisata Alam Sungai Kembang for Senior High School Student Grade X - Nanda Maisyura; Aulia Ajizah; Sri Amintarti (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2021)
Media in biology learning is one of the means so that students understand the concept of biology in a broad sense. Most students still find it difficult to understand the concept of biology, especially in the Bryophytes sub-concept because of the lack of local potential-based references that are directly related to student life. This encourages researchers to develop learning media in the form of booklets on the Bryophytes sub-concept Plantae. The purpose of this study was to describe the results of the validity of the Bryophytes booklet on the banks of the wisata alam Sungai Kembang as a high school learning medium for Grade X. This study used descriptive research methods and 4D model development methods. The validation test was carried out by experts consisting of 2 validators with an overall validity value of 84.21% with very valid criteria and suitable for use as a learning medium.Abstrak Media dalam pembelajaran Biologi merupakan salah satu sarana agar peserta didik memahami konsep pada Biologi secara luas. Kebanyakan peserta didik masih sulit untuk memahami konsep Biologi terutama pada sub konsep Bryophyta karena kurangnya referensi berbasis potensi lokal yang berkaitan langsung dengan kehidupan siswa. Hal tersebut mendorong peneliti untuk mengembangkan media pembelajaran berupa booklet materi Plantae sub konsep Bryophyta. Tujuan penelitian ini adalah untuk mendeskripsikan hasil validitas booklet Bryophyta di bantaran sungai wisata alam Sungai Kembang sebagai media pembelajaran SMA untuk Kelas X. Penelitian ini menggunakan metode penelitian deskriptif dan metode pengembangan model 4D. Uji validitas dilakukan oleh para ahli yang terdiri dari 2 validator dengan nilai validitas keseluruhan yaitu 84,21% dengan kriteria sangat valid dan layak digunakan sebagai salah satu media belajar.